Fraud Control Plan System: The Role Investigation Division In Fraud Prevention - Setiawan, Desy Amaliati; Mais, Rimi Gusliana; Kurniawan, Rachmad Risqy; Sari, Hastuti Indra (Labkat Press KA FTIK UNIKOM, 2024)
The Financial and Development Supervisory Agency (BPKP) has an important and vital role in preventing corruption and fraud to create good governance that can be implemented in all government agencies. BPKP has made integrated efforts to prevent fraud and corruption, but in its implementation, there are still obstacles so that the achievement is considered less than optimal. This study aims to see the role of the Investigation Division of BPKP in preventing fraud by using the Fraud Control Plan (FCP) which consists of 10 attributes, namely: anti-fraud policy, anti-fraud structure, standards of behavior and discipline, fraud risk assessment, human resource management, third party management, whistleblowing system, proactive detection, investigation, and corrective action by conducting socialization of the use of FCP, diagnostic assessment, technical guidance, and evaluation. This study is a type of qualitative research, with data collection: interviews, observations, and documentation. Interviews were conducted with 3 key informants of BPKP Jakarta employees who work in the Investigation Division. The results of this study indicate that the Investigation Division has intensified fraud prevention by using the FCP. However, there are still agencies that are less concerned about this. The BPKP Investigation Division, by using the Fraud Control Plan, hopes to provide a major role and impact on fraud prevention, by mitigating, and facilitating the disclosure of fraudulent actions and it is recommended that every agency use and implement it to create an anti-fraud environment.